AN EMPIRICAL ANALYSIS ON CONSUMER’S ATTITUDE AND PURCHASE INTENTIONS TOWARDS ORGANIC FOOD PRODUCTS (International Journal of Food and Nutritional Sciences, 2022)
This study attempted to gain knowledge about consumer’s attitude and intention to purchase organic food products. A total of 200 respondents were generated. Result indicated that the intention to purchase organic products were heavily influenced by the perception on organic product worth of purchase and the belief on the safety and health aspect of the product. Among the organic buyers majority consumers believed organic food to be healthier, tastier and better for environment compared to conventional food. It has great implication for promoting organic food markets, domestically as well as globally.